Factors affecting organizational commitment among academicians of tertiary institutions - Sakiru, Oladipo Kolapo; Ismail, Ismi Arif; Abu Samah, Bahaman; Arshad, Mohd Mursyid; Busayo, Oladipo Temitope (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The study was carried out to establish the relationship between organizational commitment and the factors affecting organizational commitment among lecturers of tertiary institutions in Lagos State, Nigeria. The main problem that called for this research was to ascertain whether the level of lectures commitment affect or influence their level of satisfaction, involvement and perceived organizational commitment of lecturers in tertiary institutions in Lagos state, Nigeria. A standard self-administered questionnaire were employed to gather data among 404 selected lecturers from the tertiary institutions in Lagos state, Nigeria, based on Cochran (1977) formula for sample size determination that was used to calculate for the sample size. Descriptive analysis and Structural Equation Modelling (SEM) was conducted for data analysis. It was revealed that most of the respondent reported moderate in their response on the constructs: Organizational commitment, with (Mean=3.17, SD=0.86), leadership styles with (Mean=3.55, SD=0.84). Perceived organizational support is moderate (M=3.32, SD=0.81). These results mean that tertiary institutions lecturers have rated moderate in explaining their leadership styles, perceived organizational support and organizational commitment of their institutions. Also Overall score for job involvement satisfaction are moderate at (M=3.56 SD=0.90). Structural Equation Model analysis results respectively, indicated that there is positive significant relationship between the organizational commitment. leadership styles, perceived organizational support and job involvement. In conclusion, it is recommended that practitioner, government and society should take great focus on perceived organizational support, job involvement, as well as leadership styles in order to improve academic staff organizational commitment. At the same time, reduce the turnover rate among lecturers of tertiary institutions in Lagos state, Nigeria.